The interacting effects of ungulates and fire on forest dynamics: an analysis using the model FORSPACE - Kramer, K.; Groen, T.A.; van Wieren, S.E. (Forest ecology and management, 2003)
The effects of interactions between the density of ungulates and forest fires on forest dynamics were studied on an area of 1188 ha called Planken Wambuis. The vegetation consists mainly of heathland and Scots pine forest but also includes oak, beech and birch, and parts of former arable land that is now covered with grass. The ungulate species considered are bovine, horse, red deer, roe deer and wild boar. The spatially explicit and process-based model FORSPACE was used for this analysis. FORSPACE is a forest gap-dynamics model that includes a mechanistic description of ungulate dynamics and a stochastic forest fire simulator. The scenarios analysed included three levels of ungulate density (no ungulates, low density due to population regulation by management, high density due to absence of regulation), and three levels of ignition frequency of wild fires (zero, low and high). The simulation results indicate that fires at high ignition frequency may shift the system into a different stable state in the phase plane of producers (represented by total ecosystem foliage biomass) versus consumers (represented by total ecosystem ungulate biomass). This pattern was found both at low and high ungulate densities, although the effect is more pronounced at high ungulate density. Grazing is predicted to reduce the occurrence of both small and large-scale wild fires by reducing fuel load and altering the vertical structure of the vegetation. This occurs even at low ungulate densities and is most pronounced at high ignition frequencies. The ungulate consumption and plant production figures predicted by the model fall within the ranges that are presented in the literature for temperate forest ecosystems. For the scenarios with regulated ungulate densities the ungulate biomass per unit area are of the same magnitude as found in temperate forest ecosystems. However, if ungulate densities are not regulated by management, the model results suggest that the ungulate biomass per unit area may increase two-fold.